A MOTIVATIONAL ANALYSIS OF THE MIMETIC CHARACTERS OF MA AND CHEEL IN TEHMINA DURRANI’S NOVEL BLASPHEMY - Baseer, Abdul; Awan, Muhammad Safeer (European Scientific Journal, ESJ, 2012)
The discussion on the relative importance of the „character‟ versus „plot‟ in literary works is endless and still going-on. From Aristotle to the present day, every theorist has his own theoretical perspective on this issue depending on his own understanding of the nature, function, and aim of literature in society. Aristotle, A.C. Bradley, E.M. Forster, structuralist narratologists, modern psychoanalysts, and recent cognitive narratologists have been talking about and still arguing for or against the relative importance of „character‟ against „plot‟. Marvin Mudrick, and Robert Scholes & Robert Kellogg categorize the character as „semiotic/mimetic’, and ‘aesthetic/illustrative/mimetic’ respectively. Mudrick and Scholes & Kellogg‟s mimetic category refers to the realistic form of literature. Such characters exist in realistic literature, and they must be treated as near to real human beings because they are independent entities having their inner life and motivations, and they guide the plot and theme, not the other way round, in a literary piece of art. Such characters cannot be analyzed in structuralists‟ theoretical terms, as they are considered as independent entities, and not as a structural part of the plot. Considering Tehmina Durrani‟s novel Blasphemy a realist novel in Pakistani setting, this paper presents a motivational analysis of two of its characters, Ma and Cheel. Ma is an expansive (perfectionist) person, and Cheel‟s character transforms from perfectionist to arrogant-vindictive. Nonetheless, she displays compliant attitude only towards Heer.